齿形链传动的模态仿真分析 - 王勇; 朱冬伟; 薛云娜 (Jixie chuandong)
Silent chain drive is a kind of transmission mechanism with a lot of flexible plates. It is difficult to calculate the natural frequencies of silent chain drive accurately because of the discontinuity of its structure and the polygonal effect. The flexible plates of chain of chain drive in the tension side is translated to the mechanical model with lumped mass based on the software ANSYS. The lumped mass element approach is used to analyze the natural frequency and the modal in the ANSYS. The results of the analysis match better with the theoretical results.